Artificial cells for the treatment of liver diseases. (August 2021) - Zou, Da; Wang, Haolu; Liu, Xin; Xu, Zhi Ping; Roberts, Michael S.; Zhao, Chun-Xia
Abstract: Liver diseases have become an increasing health burden and account for over 2 million deaths every year globally. Standard therapies including liver transplant and cell therapy offer a promising treatment for liver diseases, but they also suffer limitations such as adverse immune reactions and lack of long-term efficacy. Artificial cells that mimic certain functions of a living cell have emerged as a new strategy to overcome some of the challenges that liver cell therapy faces at present. Artificial cells have demonstrated advantages in long-term storage, targeting capability, and tuneable features. This article provides an overview of the recent progress in developing artificial cells and their potential applications in liver disease treatment. First, the design of artificial cells and their biomimicking functions are summarized. Then, systems that mimic cell surface properties are introduced with two concepts highlighted: cell membrane-coated artificial cells and synthetic lipid-based artificial cells. Next, cell microencapsulation strategy is summarized and discussed. Finally, challenges and future perspectives of artificial cells are outlined. Statement of significance: Liver diseases have become an increasing health burden. Standard therapies including liver transplant and cell therapy offer a promising treatment for liver diseases, but they have limitations such as adverse immune reactions and lack of long-term efficacy. Artificial cells that mimic certain functions of a living cell have emerged as a new strategy to overcome some of the challenges that liver cell therapy faces at present. This article provides an overview of the recent progress in developing artificial cells and their potential applications in liver disease treatment, including the design of artificial cells and their biomimicking functions, two systems that mimic cell surface properties (cell membrane-coated artificial cells and synthetic lipid-based artificial cells), and cell microencapsulation strategy. We also outline the challenges and future perspectives of artificial cells. Graphical abstract: Image, graphical abstract